Investıgatıon Of The Rıcketts’ ‘Measurments Used In The Predıctıon Of Lower Thırd Molars Eruptıon - Aslı Ender Telli (Turkish Journal of Orthodontics, 1997)

(untitled)
In this study the validity of the RO/8 ratio and Xi-7 mm measurments suggested by Ricketts in the prediction of lower third molars eruption are investigated. These measurments are made on the lateral cephalograms of 40 cases including 20 males and 20 females between the ages of 17-21. The possibility of the eruption and impaction of the lower third molars is predicted by means of logistic regression analysis method. The 71 segments in which the lower third molars were present but erupted consisted our study grup. it is observed that in 33 of 71 segments the lower third molars were erupted at the end Off the third year. The specificity of the test is found as %90.91, and its sensivity is found as %94.74 when we have compared the values observed at the end of the research with the values obtained using the logistic regressin analysis. The contribution of the RO/8 ratio to our model was found less important than the Xi-7 measur-metnts. the selectivity is found as %84.85 when the Xi-7 measurnment is used alone but the sensivity is unchanged. It is found that the use of both of these measurements in the prediction of lower sensivity is unchanged. It is found that the use of both of these measurements in the prediction of lower third molars would be more meaningful.